2022
DOI: 10.3390/c8020021
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Nanostructured Carbon Catalyst Supports for the Continuous Reduction of Bromate in Drinking Water

Abstract: Recent works in the development of nanostructured catalysts for bromate reduction in drinking water under hydrogen have highlighted the importance of the properties of the metallic phase support in their overall performance. Since most works in catalyst development are carried out in powder form, there is an overlooked gap in the correlation between catalyst support properties and performance in typical continuous applications such as fixed bed reactors. In this work, it is shown that the mechanical modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The significance of this final factor is pivotal for the overall functionality of the catalyst. An investigation focused on determining the quantity of H 2 needed to activate the catalyst by varying H 2 flow rates from 5 to 75 cm 3 min −1 revealed a generally consistent activation pattern, except for a flow rate of 5 cm 3 min −1 [4]. Therefore, the determination of the H 2 flow rate is an important step since, as mentioned earlier and as suggested in the literature, the reaction mechanism involves the dissociative adsorption of H 2 on the surface of the metallic catalyst and the reaction between the adsorbed bromate ions and the atoms of hydrogen [3].…”
Section: Bromate Reduction Over Magnetic Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…The significance of this final factor is pivotal for the overall functionality of the catalyst. An investigation focused on determining the quantity of H 2 needed to activate the catalyst by varying H 2 flow rates from 5 to 75 cm 3 min −1 revealed a generally consistent activation pattern, except for a flow rate of 5 cm 3 min −1 [4]. Therefore, the determination of the H 2 flow rate is an important step since, as mentioned earlier and as suggested in the literature, the reaction mechanism involves the dissociative adsorption of H 2 on the surface of the metallic catalyst and the reaction between the adsorbed bromate ions and the atoms of hydrogen [3].…”
Section: Bromate Reduction Over Magnetic Nanoparticlesmentioning
confidence: 99%
“…This indicates that the presence of other ions and organic matter influences the catalytic activity. The mechanism of bromate reaction is revealed to be a process controlled via adsorption, and therefore, the presence of ions can trigger competition for adsorption on the active sites of the metal, inhibiting the reduction of bromate [4]. Chen et al [20], when carrying out bromate reduction experiments in the presence of SO 4 2− , Cl − , and Br − ions to evaluate the impact of these anions, observed that the SO 4 2− ion, compared to Cl − and Br − , has a higher ionic charge.…”
Section: Before Reactionmentioning
confidence: 99%
See 1 more Smart Citation